ELECTRONIC BUSINESS CONCEPT IN MARKETING OF VILLAGE LEADING PRODUCTS - Yudo Devianto; Saruni Dwiasnati (IJISCS (International Journal of Information System and Computer Science), 2020)
In preparing to welcome the era of technology 4.0, especially preparing rural communities to be ready to accept the arrival of the era of technology 4.0, how can rural communities utilize the technology for their interests. Especially how rural communities can promote superior products produced by the community in general as well as rural communities in particular by using these technologies. In this research, it will be discussed how the application of E-Business can help marketing superior village products, and based on the mandate of law number 6 of 2014 "About the Village", article 86 "Information Systems for Rural Development and Rural Area Development". The problems faced, among others, are many villages that have not been touched by information technology, many villages that have superior products have not been touched by information technology, the potential, and superior products of the village are not fully promoted so that the potential and village products are not widely known. The purpose of the research is to provide the best solution so that the existing problems can be resolved, of course by utilizing information technology, which is a web-based application, by incorporating the concept of E-Business in the application to be made. The results of this study are the application of B2B and B2G E-Business to support the creation of E-Marketing Applications that can be used as solutions to problems that occur.